2016
DOI: 10.2519/jospt.2016.6713
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Rotation in Femoroacetabular Impingement Is Decreased Compared to Other Symptomatic Hip Conditions

Abstract: Study Design Cross-sectional, case-control design. Background Pelvic movement has been considered a possible discriminating parameter associated with femoroacetabular impingement (FAI) symptom onset. Decreased pelvic rotation has been found during squatting in people with FAI when compared to people with healthy hips. However, it is possible that changes in pelvic movement may occur in other hip conditions because of pain and may not be specific to FAI. Objectives To compare sagittal pelvic rotation during hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To be included an article had to quantitatively describe movement of both the thigh and pelvis during hip flexion. Articles were excluded if they described the position of the thigh and pelvis during the static maintenance of hip flexion or during complex activities such as walking 1 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be included an article had to quantitatively describe movement of both the thigh and pelvis during hip flexion. Articles were excluded if they described the position of the thigh and pelvis during the static maintenance of hip flexion or during complex activities such as walking 1 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researchers have described the kinematics of the movement and in doing so have noted that it is multifaceted. Specifically, it involves a simultaneous movement of the thigh (femur) on the pelvis and a posterior tilting of the pelvis (PTT) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ) , together known as pelvifemoral rhythm. It also involves a flattening of the lumbar spine 11 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have not found differences in alignment and movement patterns between healthy people and people with musculoskeletal symptoms, 39 , 40 others have found significant differences. 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Patellofemoral pain is related to increased peak hip adduction, internal rotation and contralateral pelvic drop. 46 Studies assessing kinematics of the shoulder complex have identified differences between people with and people without shoulder pain.…”
Section: Impairments Of Alignment and Movement In People With Musculomentioning
confidence: 99%
“… 42 People with femoroacetabular impingement have different pelvic movement during hip flexion movements compared to healthy subjects. 41 , 43 , 48 People with low back pain move their lumbopelvic region to a greater extent and earlier during lower limb movements than people without low back pain. 17 , 47 …”
Section: Impairments Of Alignment and Movement In People With Musculomentioning
confidence: 99%
“…24 For example, hip ROM limitations associated with cam morphology has been linked to increased motion and stress at the pubic symphysis 25,26 Aside from morphology, regional contributions may also affect hip mobility, as the posture of the pelvis can further reduce the ROM available at the hip 27 while those with FAI syndrome demonstrate a decreased ability to functionally rotate the pelvis posteriorly. 28 It has been suggested that the relationship of FAI and the lumbopelvic region play a role in LBP. 2,12,14 The mobility of soft tissue structures surrounding the hip joint can also contribute to functional losses in ROM.…”
Section: Introductionmentioning
confidence: 99%